2019
DOI: 10.1055/s-0039-3400747
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood del Nido versus Cold Blood Microplegia in Adult Cardiac Surgery: A Propensity-Matched Analysis

Abstract: Objectives Few studies have evaluated the outcomes of whole blood microplegia in adult cardiac surgery. Our novel protocol includes removing the crystalloid portion and using the Quest Myocardial Protection System (MPS) for the delivery of del Nido additives in whole blood. This study sought to compare early and late clinical outcomes of whole blood del Nido microplegia (BDN) versus cold blood cardioplegia (CBC) following adult cardiac surgery. Methods A total of 361 patients who underwent cardiac su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They reported that MDNC was safe in high-risk patients undergoing cardiac surgery and in prolonged operations. The same group compared their MDNC strategy with lidocaine containing CBC [ 9 ] . They found comparable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that MDNC was safe in high-risk patients undergoing cardiac surgery and in prolonged operations. The same group compared their MDNC strategy with lidocaine containing CBC [ 9 ] . They found comparable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline information of the patients, such as demographic data, blood parameters, serum glutamic pyruvic transaminase (SGPT), serum glutamic oxaloacetic transaminase (SGOT), serum bilirubin, blood urea, and left ventricular ejection fraction, were extracted from the medical records. The definitions used for the study are from the Society of Thoracic Surgeons National Cardiac Surgery Database [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pre-operative demographic data including, name, gender, age, weight, height, body mass index, history of smoking, and presence of diabetes mellitus were retrieved from the database. The Society of Thoracic Surgeons National Cardiac Surgery Database definitions were used for this study [ 6 ]. Prolonged ventilation was defined as “pulmonary insufficiency requiring a ventilator for >24 h, postoperatively”.…”
Section: Methodsmentioning
confidence: 99%
“…The ingredients of DNC are mixed with highly oxygenated blood and crystalloid solution with a ratio of 4 times crystalloid to 1 times blood [ 5 ]. However, the Brigham group used it with a ratio of 8:1 (blood to crystalloid) composition [ 6 ]. Due to the ease of administering, single induction dose, and the value of decreasing surgical interruption, its use in adult cardiac surgery gained acceptance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%